Expression of the collagen adhesin ace by Enterococcus faecalis strain OG1RF is not repressed by Ers but requires the Ers box. Issue 1 (1st May 2013) - Cohen, Ana Luisa V.; Roh, Jung Hyeob; Nallapareddy, Sreedhar R.; Höök, Magnus; Murray, Barbara E.
Abstract Expression of adhesin to collagen of Enterococcus faecalis (ace), a known virulence factor, is increased by environmental signals such as the presence of serum, high temperature, and bile salts. Currently, the enterococcal regulator of survival (Ers) of E. faecalis strain JH2‐2 is the only reported repressor of ace. Here, we show that for strain OG1RF, Ers is not involved in the regulation of ace. Our data showed similar levels of ace expression by OG1RF and its Δers derivative in the presence of bile salts, serum, and high temperature. Using ace promoter‐lacZ fusions and site‐directed mutagenesis, we confirmed these results and further showed that, while the previously designated Ers box is important for increased expression from the ace promoter of OG1RF, the region responsible for the increase is bigger than the Ers box. In summary, these results indicate that, in strain OG1RF, Ers is not a repressor of ace expression. Although JH2‐2 and OG1RF differ by six nucleotides in the region upstream of ace as well as in production of Fsr and gelatinase, the reason(s) for the difference in ace expression between JH2‐2 and OG1RF and for increased ace expression in bile, serum and at 46 °C remain(s) to be determined.